2018
DOI: 10.1073/pnas.1721022115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maturation on the conformational free-energy landscape of SOD1

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating fatal syndrome characterized by very rapid degeneration of motor neurons. A leading hypothesis is that ALS is caused by toxic protein misfolding and aggregation, as also occurs in many other neurodegenerative disorders, such as prion, Alzheimer's, Parkinson's, and Huntington's diseases. A prominent cause of familial ALS is mutations in the protein superoxide dismutase (SOD1), which promote the formation of misfolded SOD1 conformers that are prone to aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 61 publications
(66 reference statements)
7
66
1
Order By: Relevance
“…Although there are multiple reports reflecting upon the importance of the electrostatic loops [21][22][23][24] in SOD1 and the role of metal ions in terms of crafting the structural integrity in SOD1, there is a lack of understanding as to how these residues are interdependent and whether they are under evolutionary selection pressure. Deploying co-evolution analysis on a wide array of sequences, we have been able to retrieve residues which are co-evolving and, hence, evolutionarily coupled.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are multiple reports reflecting upon the importance of the electrostatic loops [21][22][23][24] in SOD1 and the role of metal ions in terms of crafting the structural integrity in SOD1, there is a lack of understanding as to how these residues are interdependent and whether they are under evolutionary selection pressure. Deploying co-evolution analysis on a wide array of sequences, we have been able to retrieve residues which are co-evolving and, hence, evolutionarily coupled.…”
Section: Introductionmentioning
confidence: 99%
“…While the disulfide-intact, metal-bound SOD1 dimer is remarkably stable and resistant to aggregation (9), mutations are known to destabilize the native dimer and increase the populations of folded and unfolded forms of the monomeric protein that may nucleate aggregation (10)(11)(12)(13)(14). Several studies have suggested specific structures for such misfolded monomers and nonnative dimers (15)(16)(17)(18). However, the large number of ALS-linked SOD1 mutations and, in particular, their distribution throughout the sequence, motivated us to propose a general explanation for the aggregation phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have developed an assay allowing one to follow rapid and reproducible SOD1 kinetics at physiological pH (see Methods section). One key component used in the assay is a disulfide reducing agent, since disulfide reduction in SOD1 leads to destabilization of the SOD1 dimer and facilitates fibrillization (Furukawa, Torres & O'Halloran, 2004;Sheng et al, 2013;Culik et al, 2018). Another key component is guanidine hydrochloride (GuHCl), a chaotropic agent that accelerates SOD1 aggregation (Sheng et al, 2013) and in our case, strongly promotes SOD1 fibrillization and prevents "off-pathway" oligomer formation (Fig.…”
Section: Development Of Sod1 Aggregation Assaymentioning
confidence: 96%